After the DMA, the DSA and the New AI regulation: Mapping the economic consequences of and responses to new digital regulations in Europe - Fredrik Erixon; Oscar Guinea; Erik Van der Marel; Elena Sisto (European Centre for International Political Economy (ECIPE), 2022)
The European Union (EU) has pursued an ambitious agenda for regulating the digital economy, and it is now planning to establish a new package of regulations, including the Digital Markets Act (DMA), the Digital Services Act (DSA), and a new regulation of Artificial Intelligence (AI). These regulations build on an already established structure of digital and business regulations in Europe that is comparatively restrictive but that varies substantially between EU member states. In this study, we take stock of the new incoming regulations and review their effect on EU member states' economies. More precisely, the paper considers how different countries in Europe will be affected by the regulations and how they should balance these effects with policies that help the economy to prosper.
Keywords: 330; Electronic commerce; online trade; regulation; impact analysis; EU states; Electronic Commerce; Online-Handel; Regulierung; Wirkungsanalyse; EU-Staaten